2007
DOI: 10.1002/jcb.21281
|View full text |Cite
|
Sign up to set email alerts
|

Dp71ab/DAPs complex composition changes during the differentiation process in PC12 cells

Abstract: PC12 cells express different Dp71 isoforms originated from alternative splicing; one of them, Dp71ab lacks exons 71 and 78. To gain insight into the function of Dp71 isoforms we identified dystrophin associated proteins (DAPs) that associate in vivo with Dp71ab during nerve growth factor (NGF) induced differentiation of PC12 cells. DAPs expression was analyzed by RT-PCR, Western blot and indirect immunofluorescence, showing the presence of each mRNA and protein corresponding to alpha-, beta-, gamma-, delta-, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Previously, we demonstrated that the Dp71f variant modulates the adhesion of PC12 cells by interacting with the b1-integrin adhesion protein complex and by this way conferring stability to this complex. Furthermore, it has been reported that Dp71f associates with b-dystroglycan, a1-syntrophin and b-dystrobrevin in the cytoplasm of the PC12 cells to constitute a dystrophin-associated protein complex (DAPC) [36]. These authors propose that the cytoplasmic DAPC is involved in the cytoskeleton network modeling that occurs during the NGF-induced neuronal differentiation of PC12 cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previously, we demonstrated that the Dp71f variant modulates the adhesion of PC12 cells by interacting with the b1-integrin adhesion protein complex and by this way conferring stability to this complex. Furthermore, it has been reported that Dp71f associates with b-dystroglycan, a1-syntrophin and b-dystrobrevin in the cytoplasm of the PC12 cells to constitute a dystrophin-associated protein complex (DAPC) [36]. These authors propose that the cytoplasmic DAPC is involved in the cytoskeleton network modeling that occurs during the NGF-induced neuronal differentiation of PC12 cells.…”
Section: Discussionmentioning
confidence: 96%
“…We [17,19], and others [18,35,36], have adopted the PC12 cell line as in vitro neuronal model for studying the function of Dp71. These cells express two Dp71 isoforms called Dp71d and Dp71f, which display different subcellular localization each other [18].…”
Section: Discussionmentioning
confidence: 99%
“…Romo-Yáñez et al [2007] detected gene expression of all known SGs ( ␣ -, ␤ -, ␥ -, ␦ -, -and -SG) and confirmed the expression of the proteins by indirect immunofluorescence. Our results in the normal human cerebral cortex evidenced the existence of all proteins that characterized the complex ( ␣ , ␤ , ␦ , ␥ , This study documented the presence of all SGs tested, even in astrocytes of the premotor area.…”
Section: μMmentioning
confidence: 93%
“…These results suggest that exons 71-74 play an important role in the cytoplasmic localization of Dp71a and Dp71e isoforms because Dp71c and Dp71ec, which lack these exons, do not show cytoplasmic localization. Most likely, each Dp71 isoform forms a specific complex with the membrane, cytoplasm, or nuclear proteins because Dp71-DAP complexes have been described in the end-feet and cell membranes of retina Müller glial cells (Fort et al 2008) and in the cytoplasm and nuclei of several cell line models (Fuentes-Mera et al 2006;Romo-Yáñez et al 2007;González-Ramírez et al 2008;Villarreal-Silva et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that β-dystroglycan and α1-syntrophin colocalize and interact with Dp71ab in PC12 cells (Romo-Yáñez et al 2007). To determine if β-dystroglycan formed complexes with the recombinant Dp71 isoforms, colocalization assays were performed.…”
Section: Colocalization Of Myc-dp71 Proteins With β-Dystroglycan and mentioning
confidence: 99%